Recent advances in cytogenetic characterization of multiple myeloma. (3rd July 2018) - Saxe, Debra; Seo, Eul‐Ju; Beaulieu Bergeron, Melanie; Han, Jin‐Yeong
Abstract: The detection of cytogenetic abnormalities in multiple myeloma (MM) has received more importance over last years for risk stratification and the new risk‐adapted treatment strategies. Conventional G‐banding analysis should be included in a routine procedure for the initial diagnostic workup for patients suspected of MM. However, the detection of chromosomal abnormalities in MM by conventional cytogenetics is limited owing to the low proliferative activity of malignant plasma cells as well as the low number of plasma cells in bone marrow specimens. Fluorescence in situ hybridization (FISH) or microarray‐based technologies can overcome some of those drawbacks and detect specific target arrangements as well as chromosomal copy number changes. In this review, we will discuss different cytogenetic approaches and compare their strength and weakness to provide genetic information for risk stratification and prediction of outcome in MM patients.